A differential mobility spectrometry/mass spectrometry platform for the rapid detection and quantitation of DNA adduct dG‐ABP. (21st May 2013) - Kafle, Amol; Klaene, Joshua; Hall, Adam B.; Glick, James; Coy, Stephen L.; Vouros, Paul
<x xml:space="preserve">Abstract</x> RATIONALE There is continued interest in exploring new analytical technologies for the detection and quantitation of DNA adducts, biomarkers which provide direct evidence of exposure and genetic damage in cells. With the goal of reducing clean‐up steps and improving sample throughput, a Differential Mobility Spectrometry/Mass Spectrometry (DMS/MS) platform has been introduced for adduct analysis. METHODS A DMS/MS platform has been utilized for the analysis of dG‐ABP, the deoxyguanosine adduct of the bladder carcinogen 4‐aminobiphenyl (4‐ABP). After optimization of the DMS parameters, each sample was analyzed in just 30 s following a simple protein precipitation step of the digested DNA. RESULTS A detection limit of one modification in 10^6 nucleosides has been achieved using only 2 µg of DNA. A brief comparison (quantitative and qualitative) with liquid chromatography/mass spectrometry is also presented highlighting the advantages of using the DMS/MS method as a high‐throughput platform. CONCLUSIONS The data presented demonstrate the successful application of a DMS/MS/MS platform for the rapid quantitation of DNA adducts using, as a model analyte, the deoxyguanosine adduct of the bladder carcinogen 4‐aminobiphenyl. Copyright © 2013 John Wiley & Sons, Ltd.